Pengembangan Model Pembelajaran NHT (Numbered Heads Together) Terintegrasi Games Pada Mata Pelajaran Bahasa Indonesia - Ica Novita Sari; Edhy Rustan; Muhammad Ihsan (Institut Agama Islam Tribakti Kediri, 2022)
Learning is a process of delivering knowledge carried out by the teacher. In the The objective of this developing approach is to understand the description of the needs analysis of the games-integrated Numbered Heads Together (NHT) learning model in Bahasa Indonesia subject, how to design games-integrated Numbered Heads Together (NHT) learning model in Bahasa Indonesia subject, and to measure the validity of games-integrated Numbered Heads Together (NHT) learning model. The type of this research is R&D and was developed using the ADDIE model which consists of the analysis, design, development, implementation, and evaluation stages. The data collection technique was carried out using interview guidelines given to fifth grade teachers to find out the curriculum used, and the problems experienced by the teacher during the learning process. As for the use of questionnaires and student knowledge tests, they were given to fifth grade students of SDN 9 Matekko as subjects to measure the level of understanding, knowledge and learning abilities of students. Needs analysis using tests showed that students lack of understanding of the essay material resulted in a score below the Cut Score Grading (KKM), and student questionnares showed that students liked the learning model that was carried out in groups and integrated with games. The design of the games-integrated NHT learning model is in the form of a guidebook that contains detailed syntax according to the learning objectives. The validity of the games-integrated NHT learning model showed valid result with a score of 79% for design validation, and very valid with a score of 90% for language validation, and 91% for validation of the learning model implementation [Tujuan dilakukannya pengembangan ini adalah untuk mengetahui deskripsi analisis kebutuhan model pembelajaran NHT (Numbered Heads Together) terintegrasi games pada mata pelajaran Bahasa Indonesia, mengetahui perancangan model pembelajaran NHT (Numbered Heads Together) terintegrasi games, dan mengetahui tingkat kevalidan model pembelajaran NHT (Number Heads Together) terintegrasi games. Jenis penelitian ini adalah R&D dan dikembangkan dengan menggunakan model ADDIE yang terdiri dari tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Teknik pengumpulan data dilakukan dengan menggunakan pedoman wawancara yang diberikan kepada guru kelas V guna mengetahui kurikulum yang digunakan, dan masalah-masalah yang dialami guru selama proses pembelajaran. Adapun penggunaan angket dan tes pengetahuan siswa, diberikan kepada siswa kelas V SDN 9 Matekko sebagai subyek untuk mengukur tingkat pemahaman, pengetahuan dan kemampuan belajar siswa. Analisis kebutuhan menggunakan tes menunjukkan hasil bahwa kurangnya pemahaman siswa mengenai materi karangan sehingga diperoleh nilai dibawah KKM, dan angket siswa diperoleh hasil bahwa siswa menyukai model pembelajaran yang dilakukan secara berkelompok dan diintegrasikan dengan games. Perancangan model pembelajaran NHT terintegrasi games berupa buku panduan yaitu berisi sintaks yang dirinci sesuai dengan tujuan pembelajaran. Kevalidan model pembelajaran NHT terintegrasi games menunjukkan hasil valid dengan perolehan skor 79% untuk validasi desain, dan sangat valid dengan perolehan skor 90% untuk validasi bahasa, dan 91% untuk validasi penerapan model pembelajaran]